Development of Animated Videos on Basic Chemistry Laws as Digital Learning Media - Lilik Yuninnur; Fitriani; Hamdil Mukhlishin (Jurnal Penelitian Pendidikan IPA, 2025)
This research aims to develop animated videos media as a digital learning medium to support students’ understanding of the basic laws of chemistry. The study employs the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The develop media is validated by matter experts, media experts, and linguists as well as small-scale and large-scale trials by students. Validation results indicated that the animated videos were included in the category of “Very Valid”, while results of the practicality test by teachers and students placed the media in the category of “Very Practical”. Based on these results, the animated videos are considered very valid and very practical for use as a digital learning medium for improving students’ understanding of the basic laws of chemistry at Taman Mulia Kubu Raya High School.